The militarization of security. A systems theory perspective. Issue 3 (3rd July 2019) - Bonacker, Thorsten
ABSTRACT: This conceptual article develops a theoretical argument for how the militarization of security can be understood from a systems theory perspective, which allows a conceptual link between the two main perspectives on militarization within securitization studies to be made. Whereas in securitization studies the so called Copenhagen School and the more sociological approach of the Paris School are generally seen as two analytical lenses on securitization and militarization, I suggest reconceptualizing them as two perspectives on empirically distinct processes of militarization. These processes occur in two different types of social systems, namely the political system on the one hand and security organizations on the other. This helps to distinguish between political and non-political forms of militarization. Although the article is concentrated on developing a theoretical perspective on the complexities of political and non-political militarization of security, it aims to encourage further exploration of how those forms of militarization are empirically interlinked.